Effect analysis of radiofrequency catheter ablation in the treatment of 7 children with atrial tachycardia-induced cardiomyopathy - Min Zhang; Xiaoxiao Cao; Suqiong Ji; Mohammadreza Kosari; Yong Zhang (Journal of Cardiothoracic Surgery)
Abstract Background Tachycardia-induced cardiomyopathy refers to changes in cardiac structure and function that result from rapid arrhythmia and can manifest as a continuous or recurrent event. Cardiomyopathy induced by atrial tachycardia is typically reversible if the arrhythmia is effectively controlled. There are few literature reports of atrial tachycardia-induced cardiomyopathy in children, and fewer cases have been effectively treated by radiofrequency catheter ablation in children. Objective we conducted a clinical summary of 7 cases of atrial tachycardia-induced cardiomyopathy in children in Wuhan Children’s Hospital to investigate the effectiveness and safety of radiofrequency catheter ablation for atrial tachycardia-induced cardiomyopathy. Methods A total of 7 children (4 girls and 3 boys) diagnosed with atrial tachycardia-induced cardiomyopathy and admitted to Wuhan Children’s Hospital from January 2017 to April 2024 were selected. An intracardiac electrophysiological study was conducted on all 7 children to verify the origin of the atrial tachycardia and the presence of decreased cardiac function. All children were followed up for a period ranging from 2 to 12 months after RFCA or atrial appendectomy. During this follow-up, left ventricular end-diastolic diameter and left ventricular ejection fraction were monitored. Results The age range was 3.6 to 13 years and the median age was 11.2 years. The weight range was from 15 to 92 kg, the average weight was 34 kg. The results of the intracardiac electrophysiological study of the 7 cases showed that the origin came from the right pulmonary vein in 2 cases, from the left pulmonary vein in 2 cases, from the left atrial appendage in one case, and from the right atrial appendage in 2 cases. Four cases of tachycardia-induced cardiomyopathy originating in the left and right pulmonary veins were successfully eliminated by radiofrequency catheter ablation (RFCA). The foci of atrial tachycardia were located in the atrial appendages of three children. For two of them, after precise positioning by the atrium three-dimensional electroanatomic mapping system and performing RFCA, the atrial tachycardia briefly stopped for approximately 24 h before reoccurring, and atrial appendectomy was subsequently performed. Nevertheless, in the other child, whose focus of atrial tachycardia was in the right atrial appendage, the lesion was successfully eliminated by RFCA. After RFCA or in combination with atrial appendectomy, 6 children were followed for more than 1 year and 1 child for 2 months. All children had sinus rhythm. At the same time, the left ventricular ejection fraction after RFCA or combined atrial appendectomy was significantly increased in 7 cases, indicating statistical significance (P = 0.018)), but the left ventricular end-diastolic diameter was not statistically significant in the treatment (P = 0.203)). Conclusions Sustained atrial tachycardia can lead to the occurrence of cardiomyopathy such as cardiac enlargement and heart failure. RFCA and combined atrial appendectomy can effectively stop tachycardia, eliminate the mechanism of tachycardia, and allow complete recovery of cardiac function.